2021
DOI: 10.1002/eji.202049064
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cells: Building on the CD19 paradigm

Abstract: Spearheaded by the therapeutic use of chimeric antigen receptors (CARs) targeting CD19, synthetic immunology has entered the clinical arena. CARs are recombinant receptors for antigen that engage cell surface molecules through the variable region of an antibody and signal through arrayed T-cell activating and costimulatory domains. CARs allow redirection of T-cell cytotoxicity against any antigen of choice, independent of MHC expression. Patient T cells engineered to express CARs specific for CD19 have yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 165 publications
(212 reference statements)
0
32
0
Order By: Relevance
“…T cell exhaustion (Globerson Levin et al, 2021;Watanabe et al, 2018). Our results using nanoluciferase reporters indicated that eIF3-responsive mRNA 3'-UTR elements could be used to improve chimeric antigen receptor expression and CAR T cell responsiveness (Eyquem et al, 2017;Globerson Levin et al, 2021;Watanabe et al, 2018). We used this information to improve the ability of CAR T cells to kill tumor cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T cell exhaustion (Globerson Levin et al, 2021;Watanabe et al, 2018). Our results using nanoluciferase reporters indicated that eIF3-responsive mRNA 3'-UTR elements could be used to improve chimeric antigen receptor expression and CAR T cell responsiveness (Eyquem et al, 2017;Globerson Levin et al, 2021;Watanabe et al, 2018). We used this information to improve the ability of CAR T cells to kill tumor cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Insights from these studies have also inspired efforts to engineer T cells for immunotherapy applications such as treating cancers ( Chen and Flies, 2013 ). T cells can be engineered to express chimeric antigen receptors (CARs) that specifically target antigens on the surface of cancer cells, and signal through protein elements derived from both the TCR and CD28 or other co-stimulatory receptors ( Chen and Flies, 2013 ; Globerson Levin et al, 2021 ). The most successful of these CAR T cells have been used to treat CD19-positive B cell malignancies, with dramatic results ( Friedman et al, 2018 ; Kalos et al, 2011 ; Kochenderfer et al, 2013 ; Qin et al, 2020 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturing the respective cell products for clinical application was first performed at academic centers, and then taken by commercial suppliers; however, CAR T cell manufacturing for clinical trials remains a bottleneck. Technically, T cells are engineered from the patient's leukapheresis product by a viral vector and amplified in a local or centralized good manufacturing procedure (GMP) certified facility before given back to the patient 133 . While -retroviral and lentiviral vectors are used from the beginning, now nonviral vectors systems like sleeping beauty transposon and, first in 2017, CRISPR/Cas genome editing 134 recently reported for CAR T cell engineering in vitro 135 .…”
Section: Cars Of Second Generation Are Taking the Front Seat In Clinical Explorationmentioning
confidence: 99%
“…Theoretically, it is possible to generate CAR T cells against a large number of relevant tumor antigens, nicely reviewed in (19)(20)(21)(22). Once the tumor antigen has been recognized, the CAR T cells are activated, resulting in a targeted immune reaction directed against the respective tumor.…”
Section: Cell-based Cancer Therapy: From Stem Cell Transplantation To Personalized Therapy With Car T Cellsmentioning
confidence: 99%